Places as Active Metaphors. Seaside Beaches between Empowerment and Bolkestein: in Search of a Balance - Siciliano, Sarah (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
The objective of this contribution is to critically analyze, from a socio-cultural point of view, the preliminary question of bathing establishments between the demands of free competition guaranteed by the Bolkestein directive and those of the protection, exceptional nature / cultural identity of places to empower. Everything, starting from focusing on the state of the art, using the humanities, and sociology in particular, to understand the cultural, communicative, collective, economic, social and legal implications deriving from the application of this law in Italy on bathing facilities. The reference frame of my reflection is the text of the Faro Convention, a framework convention of the European Community that looks at cultural heritage as the result of the relationship with the communities that created it, showing us that places and objects are important for the meanings and uses that we all attribute to them and for the values ​​they represent, and commits the member states to recognize cultural heritage as a right and fundamental element for "human development and the quality of life" (CETS No. 199). Through the heuristic model of the "evolving circle", a sociological data analysis tool developed by the Laboratory of Communication and Empowerment of Places of the University of Salento, the article proposes a new way of looking at the explored theme and, consequently, to interpret it in order to know every possible variable, to be evaluated case by case, overcoming dualistic or political approaches oriented from a single point of view or from visions crushed by mono-disciplinary perspectives, to direct management policies aimed at empowerment.